I. cw-Complex - Al-Khafajy, Dheia (Iraqi Journal of Science, 2024)
In this paper we introduce a new tool in algebraic topology which is called(analogous terminology of J.H.C. Whitehead in [1] ) .By studying effect of this complex on the spectral sequences , we obtained someresults , such as ;1- Any complex is an2- Let are two cw-complexes , if , then.3- If is , then.4- Let be a cw-complex , if is a , then is a, and the converse is not true .